2018
DOI: 10.3389/fpsyg.2018.02518
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metacognitive Knowledge on Mathematics Performance in Self-Regulated Learning Framework—Multiple Mediation of Self-Efficacy and Motivation

Abstract: Metacognition, self-efficacy, and motivation are important components of interaction in self-regulated learning (SRL). However, the psychological mechanism underlying the association among them in mathematical learning remained ambiguous. The present study investigated whether the relationship between metacognitive knowledge (MK) and mathematics performance can be mediated by self-efficacy and motivation. The sample comprised 569 students (245 male, Mage = 16.39, SD = 0.63) of Grade 10 in China. The MK in math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 81 publications
3
41
0
1
Order By: Relevance
“…Sabna and Hameed (2016) also confirmed that mean differences are significant and that females have higher metacognition awareness than males. Tian et al (2018) also found that there was sex differences in metacognitive knowledge but that male students scored higher than female students in metacognitive knowledge of self, and of strategies while female students scored higher in metacognitive knowledge of tasks.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Sabna and Hameed (2016) also confirmed that mean differences are significant and that females have higher metacognition awareness than males. Tian et al (2018) also found that there was sex differences in metacognitive knowledge but that male students scored higher than female students in metacognitive knowledge of self, and of strategies while female students scored higher in metacognitive knowledge of tasks.…”
Section: Resultsmentioning
confidence: 84%
“…In somewhat related findings of Kesici et al (2011) although focusing on mathematics, the results showed that declarative knowledge is a significant predictor of mathematics course achievement (which is relatively similar to the results of this study) and procedural knowledge is a significant course predictor of geometry course achievement (which is relatively different from the findings of this study). Tian et al (2018) found that mathematics performance could be predicted by metacognitive knowledge, self-efficacy and intrinsic motivation and the association between metacognitive knowledge and mathematics performance was mediated by self-efficacy and intrinsic motivation. Table 13 presents the comparison of mean responses of the different groups of students for all dimensions of metacognitive knowledge and usage.…”
Section: Resultsmentioning
confidence: 91%
“…Self-efficacy has impact on other cognitions and affect, and its influences on academic achievement behavior is also indirect (Bandura, 1997). For instance, self-efficacy proved a mediator factor of the impact of metacognition on school performance (Tian et al, 2018). Finally, to our knowledge, no study has investigated all three, metacognition, self-efficacy and hope, in prediction of school performance.…”
Section: Introductionmentioning
confidence: 89%
“…Other studies (e.g., Artelt, Schiefele, & Schneider, 2001;Veenman, Kok, & Blöte, 2005; see also Schneider, 2010) show evidence that metacognitive knowledge and self-regulation not only are determinant factors in elementary school children but also predict math performance and reading comprehension in secondary school, independent of intellectual abilities. However, the topic of metacognitive regulation, in comparison to metacognitive knowledge, has received less attention in research on mathematical learning (Neuenhaus, Artelt, Lingel, & Schneider, 2011; see also Tian et al, 2018).…”
Section: Metacognition and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation